Pengaruh Kebijakan Hutang, Ukuran Perusahaan, Dan Profitabilitas, Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Sub Sektor Consumer Non Cyclicals Di BEI Tahun 2020-2024 - Rahmi Dayulia Putri; Berta Agus Petra; Yosi Puspita Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of debt policy, firm size, and profitability on firm value with dividend policy as a moderating variable in consumer non-cyclical subsector companies listed on the Indonesia Stock Exchange during 2020–2024. Firm value is proxied by Price to Book Value (PBV), debt policy by leverage ratio, firm size by the natural logarithm of total assets, profitability by profit ratio, and dividend policy by Dividend Payout Ratio (DPR). The study uses secondary data from annual financial reports obtained from the official Indonesia Stock Exchange website and applies panel data regression with Moderated Regression Analysis (MRA) using EViews 12. Partial test results show that debt policy has a significant effect on firm value (t = −4.884942; p = 0.0000), profitability has a significant effect (t = 2.925401; p = 0.0042), while firm size is not significant (p = 0.4876). In the moderating model, the interaction between debt policy and dividend policy is significant (t = −3.323214; p = 0.0012), the interaction between firm size and dividend policy is marginally significant (t = 1.918709; p = 0.0578), and the interaction between profitability and dividend policy is not significant (t = −0.278780; p = 0.7810). The simultaneous test indicates the model is significant with an F-statistic of 14.87329. The Adjusted R² value of 0.682 indicates that 68.2% of firm value variation is explained by the variables in the model. These findings confirm that financing structure and profitability serve as important market signals, while dividend policy plays a selective moderating role.